ANALISIS LITERASI KERAGAMAN BUDAYA KEARIFAN LOKAL DALAM PEMBELAJARAN IPAS DI KELAS IV SEKOLAH DASAR - Winursiti, Ni Made; Supriatna, Encep; Uyun, Hairul (Universitas Negeri Medan, 2025)
Cultural diversity literacy and local wisdom serve as a foundation for instilling values of tolerance, appreciation for differences, and preservation of the nation's cultural heritage. This study aims to explore cultural diversity literacy and local wisdom in science learning for fourth-grade elementary students. The problem in this study is the low understanding of students in science learning related to the material of cultural diversity. This research employs a qualitative method with a descriptive approach. The subjects of this research are fourth-grade elementary students. Data collection techniques used were observation, interviews, and documentation. The data were analyzed by reducing, displaying, and concluding. The results of this study indicate that the integration of cultural diversity literacy and local wisdom in science learning for fourth-grade elementary students has great potential to improve the quality of learning. The provision of locally-based teaching materials and training for teachers is an important step. Culture-based learning can be a solution to improve the relevance of science learning to students' lives